KINERJA PELAKSANA GERDU KEMPLING DI KELURAHAN BULU LOR DAN PEKUNDEN KOTA SEMARANG - Kusumaningjati, Endah; Yuningsih, Tri; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2013)
The background of the research is the effort of Semarang state Govermentto overcome the poverty and unemployment citizen in Semarang, named “GerduKempling, the acronym of Gerakan Terpadu bidang Kesehatan, Ekonomi,Pendidikan, Infrastruktur dan Lingkungan. The focus of this research is theperformance of operators Gerdu Kempling programme, especially theimplementation programme in Bulu Lor and Pekunden District, the threat andpromoter of the programme and how to increase the performance of implementorsprogramme. The method of the research and analysing data used qualitativeresearch with intensify interview to many respondens of distinguish status in theimplementation programme and also collect the secondary data of expert’scomments form some medias in Semarang.The result of collecting datas from some interviews and secondary datasshows according by the process, the performance of operators has fulfill GerduKempling’s schedule programme. But on the other side, the outcome of operatorsprogramme are not yet reach Gerdu Kempling’s aim, that is to change thebehavior and mental attitude of citizen target. It caused of lack guidance,less ofsocialization programme and limited of fund. Some respondens suggested toincrease the fund programme, and also to expand stakeholders participation.Last, the conclution of the research are first, the performance of operators GerduKempling’s programme the implementation programme in Bulu Lor and Pekunden District bythe process, they has fulfill Gerdu Kempling’s schedule programme. But the outcome ofoperator’s performance programme are not yet reach Gerdu Kempling’s aim, that is tochange the behavior and mental attitude of citizen target. Secondly, the threat of theprogramme are lack guidance,less of socialization programme and limited of fund. Thesuggestion to promoter of the programme are increase the fund programme, and also toexpand stakeholders participation.